HUMAN RESOURCE MANAGEMENT - Valentine, Sean R.; Meglich, Patricia A.; Mathis, Robert L.; Jackson, John H. (Cengage, 2020)
Prepare for HR and career success with the book that has set the standard for excellence in human resource management. Valentine/Meglich/Mathis/Jackson's HUMAN RESOURCE MANAGEMENT, 16E offers today's most current look at HRM and its impact on the success of organizations today. A leading resource in preparing for professional HR certification, this edition ensures you are familiar with all major topics for professional examinations from the Society for Human Resource Management and Human Resource Certification Institute. You examine the latest HR research as well as HR theory in contemporary practice. This edition highlights emerging trends driving change in HRM today, including technology, globalization, competencies and HR metrics. Accompanying MindTap digital resources offer a personalized, online learning platform with a tailored presentation created by your instructor. MindTap's Learning Path Navigator guides you in completing reading assignments, annotating readings, finishing homework and checking your understanding with quizzes and assessments.